Transformasi Digital dalam Pelayanan Publik di Dispenduk Capil - Zaskia Afrina Khaliq; Hafidatus Solehah; Lutfiatul Masruroh; Naufal Hafizh W; Yogie Agung (SS&H: Studies in Social Sciences and Humanities, 2025)
To improve the quality of public services, digital transformation has become a top priority, especially at the Population and Civil Registration Office (Dispendukcapil). This sector has utilized information and communication technology (ICT) to accelerate, facilitate, and increase the transparency of population administration services. The purpose of this study is to find the elements that support and hinder digital transformation in the Dispendukcapil, as well as how this has an impact on the quality of public services. Although digital transformation offers great opportunities to improve efficiency and accuracy, limited infrastructure, low digital literacy of society, and resistance to changes in organizational culture are some of the obstacles found based on literature research and data analysis. The results show that increasing digital literacy, central and regional government collaboration, and adequate budget allocation to support digitalization are essential. Technological transformation.